Characteristics of Tonsil Patients Undergoing Surgical Procedures at Bhayangkara Hospital, Denpasar, January-June 2026 - Ida Ayu Mirah Agung; Putu Febriyanti Yogiswara; Made Mega Febryanti (Journal of Creative Power and Ambition (JCPA), 2026)
Tonsillitis is a common Ear, Nose, Throat, Head and Neck Surgery (ENT-BKL) disease that can develop into chronic tonsillitis, requiring operative measures such as tonsillectomy or adenotonsillectomy. The characteristics of patients undergoing surgical procedures need to be known as a basis for evaluating clinical services and management. This study describes the characteristics of tonsillitis patients undergoing surgical procedures at Bhayangkara Hospital, Denpasar, from January to June 2026. The study used a retrospective descriptive design utilizing secondary data from patient medical records. The sample was determined using consecutive sampling techniques according to inclusion and exclusion criteria. Analysis was conducted descriptively using frequency distribution and percentages. A total of 25 patients met the study criteria. Patients were predominantly male (56%), while women were 44%. The 3–20 year age group was the largest group diagnosed with chronic adenotonsillitis (36%) and chronic tonsillitis (36%). The 21–60 year age group was entirely diagnosed with chronic tonsillitis (28%). Tonsillectomy was performed in 64% of patients, while adenotonsillectomy was performed in 36% of patients based on clinical diagnosis. Patients were predominantly young, with a relatively balanced gender distribution. The choice of surgical procedure was based on the clinical diagnosis and age-specific tonsil and adenoid development.